2015
DOI: 10.1007/s00586-015-3959-1
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic girdle pain 3–6 months after delivery in an unselected cohort of Norwegian women

Abstract: 16 % of women that reported PP during pregnancy were found to have persistent PGP 3-6 months after the delivery. Women with risk factors for persistent PGP should be identified while pregnant, and offered a follow-up examination 3 months after delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 29 publications
0
52
0
2
Order By: Relevance
“…We found that 17% of women reporting severe or moderate PGP the final 10 weeks of pregnancy had persistent PGP 6 weeks after delivery. In a previous study, we investigated persistent PGP in another study population, and found 16% of women reporting PP during pregnancy to have persistent PGP 3-6 months after delivery [16]. Although there are some differences between the two studies regarding study design, these findings indicate that PGP that last for more than 6 weeks may tend to become persistent.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We found that 17% of women reporting severe or moderate PGP the final 10 weeks of pregnancy had persistent PGP 6 weeks after delivery. In a previous study, we investigated persistent PGP in another study population, and found 16% of women reporting PP during pregnancy to have persistent PGP 3-6 months after delivery [16]. Although there are some differences between the two studies regarding study design, these findings indicate that PGP that last for more than 6 weeks may tend to become persistent.…”
Section: Discussionmentioning
confidence: 97%
“…Although most women recover from PGP within 6 months after delivery [7][8][9], some women experience years of intermittent or persistent PGP affecting their daily life activities, ability to work and quality of life [10][11][12][13][14][15]. We have previously shown that 16% of women reporting musculoskeletal pelvic pain (PP) during pregnancy were found to have persistent PGP 3-6 months after delivery, and that the risk factors for persistent pain were age 30 years and above, both PP and LBP during pregnancy, and moderate or high disability measured by Oswestry Disability Index (ODI) during pregnancy [16].…”
Section: Introductionmentioning
confidence: 99%
“…These complaints are a frequent cause of sick leave during pregnancy [ 6 , 7 ]. Also, we found in a previous study that 16% of women with PP during pregnancy reported persistent pain that affected their daily life activities 3–6 months after delivery [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Back pain is common phenomenon in female which is experienced during postpartum and is expected to prolong for 4-6 months affecting activities of daily living. The majority of women recover from pregnancy related mechanical lumbo-pelvic pain within 6 months of delivery However, studies show that 25 % of females still have persistent non-specifi c lower back pain 2-3 years after delivery and which interferes with their daily activities (Tersi et al, 2015, Corso et al, 2016and Gausel et al, 2016.…”
Section: Introductionmentioning
confidence: 99%